Analisa Faktor-Faktor yang Mempengaruhi Inflasi di Indonesia Periode 1997:3 – 2005:2 - Fery Andrianus; Amelia Niko (Economic Journal of Emerging Markets, 2006)
Contagion Effect from Thailand crisis representing early its economics some State in ASEAN still leave over inflation burden to Indonesia. Serious of Indonesia in overcoming inflation marked with policy of inflation as targeting single to monetary authority. Successfulness this attainment target must be followed by research influencing inflation. For that, this study aim to analyze the influence factors of inflation in Indonesia and also its movement in short-range and long-range. This research background overshadowed by inflation phenomenon in Indonesia not only having an effect in short-range but also on a long term. Through analysis of Ordinary Least Squares (OLS) show that exchange rate and interest rate significant influence the inflation. Through Analysis Partial Adjustment Model (PAM) known that only interest rate influencing fast improvement of inflation in short-range and in long-range. This research used data series time (1997:3-2005:2). Keywords: Inflation, Money Supply, GDP, Exchange Rate, Interest rate.